Orally administrated Lactobacillus gasseri TM13 and Lactobacillus crispatus LG55 can restore the vaginal health of patients recovering from bacterial vaginosis - Qi, Fengyuan; Fan, Shangrong; Fang, Chao; Ge, Lan; Lyu, Jinli; Huang, Zhuoqi; Zhao, Shaowei; Zou, Yuanqiang; Huang, Liting; Liu, Xinyang; Liang, Yiheng; Zhang, Yongke; et al. (Frontiers in Immunology, 2023)
Bacterial vaginosis (BV) is a common infection of the lower genital tract with a vaginal microbiome dysbiosis caused by decreasing of lactobacilli. Previous studies suggested that supplementation with live Lactobacillus may benefit the recovery of BV, while the outcomes vary in people from different regions. Herein, we aim to evaluate the effectiveness of oral Chinese-origin Lactobacillus with adjuvant metronidazole (MET) on treating Chinese BV patients. In total, 67 Chinese women with BV were enrolled in this parallel controlled trial and randomly assigned to two study groups: a control group treated with MET vaginal suppositories for 7 days and a probiotic group treated with oral Lactobacillus gasseri TM13 and Lactobacillus crispatus LG55 as an adjuvant to MET for 30 days. By comparing the participants with Nugent scores (NS) ≥ 7 and < 7 on days 14, 30, and 90, we found that oral administration of probiotics did not improve BV cure rates (57.14% and 67.74% at day 14, 57.14% and 58.06% at day 30, 32.14% and 48.39% at day 90 for probiotic and control group respectively). However, the probiotics were effective in restoring vaginal health after cure by showing higher proportion of participants with NS < 4 in the probiotic group compared to the control group (87.50% and 71.43% on day 14, 93.75% and 88.89% on day 30, and 77.78% and 66.67% on day 90). The relative abundance of the probiotic strains was significantly increased in the gut microbiota of the probiotic group compared to the control group at day 14, but no significance was detected after 30 and 90 days. Also, the probiotics were not detected in vaginal microbiota, suggesting that L. gasseri TM13 and L. crispatus LG55 mainly acted through the gut. A higher abundance of Prevotella timonensis at baseline was significantly associated with long-term cure failure of BV and greatly contributed to the enrichment of the lipid IVA synthesis pathway, which could aggravate inflammation response. To sum up, L. gasseri TM13 and L. crispatus LG55 can restore the vaginal health of patients recovering from BV, and individualized intervention mode should be developed to improve BV cure rates.